To catch a coronet [large type] - Hitchcock, Grace (Hitchcock, Grace. Best Laid Plans, 2024)
Muriel Beau, country baker turned heiress, can't stop instigating outrage. She discards two arranged engagements, then further antagonises Kent society by publicly proposing to a baron at a ball. His rejection leaves her with no choice but to flee to the city and to secure a coronet so splendid that her peers will forget her debacles. After years of serving as a privateer under an assumed name, Captain Erik Draycott, heir to Draycott Castle and soon to assume his uncle's title of Earl, returns to his London home to find it in disrepair thanks to his long-time nemesis. A staunch bachelor intent on returning to his ship, the captain is shocked when his mentor encourages him to take a wife. But while his alleged pauper status causes the potential London brides to turn their noses up at him, the ladies of Kent have no such qualms and are eager to fill his coffers with their fathers' wealth. Caught in a whirlwind of high society and high seas, Muriel and Erik navigate a risky undertaking that threatens their futures and creating stakes that soar above the masts of Erik's ship.